2006
DOI: 10.1373/clinchem.2006.070417
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Plasma DNA as a Novel Marker of Aseptic Inflammation Severity Related to Exercise Overtraining

Abstract: Background: Circulating free plasma DNA is implicated in conditions associated with tissue injury, including exercise-induced inflammation, and thus is a potential marker for athletic overtraining. Methods: We measured free plasma DNA along with C-reactive protein (CRP), creatine kinase (CK), and uric acid (UA) in 17 recreationally trained men participating in a 12-week resistance training regimen (8 resistance multi-joint exercises selected to stress the entire musculature: bench press, squat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 31 publications
4
118
0
9
Order By: Relevance
“…Compared to the Co group, the Tr group exhibited a significant (P < 0.05) decrease in pure fiber IIA and IID CSA in the plantaris DR portion; there was also a tendency for pure fiber I and IIB CSA to decrease in this portion (P ¼ 0.08 and P ¼ 0.09, respectively). Our results are consistent with several studies which show a predominance of catabolic condition (Seene et al, 1999;Petibois et al, 2000;Seene et al, 2004) in situations with a persistent combination of excessive overload plus inadequate recovery (Jamurtas et al, 2000;Fatouros et al, 2006). Although the molecular events that underlie our findings remain unknown, these observations raise questions as to what signals and cellular conditions initiate muscle mass changes during overtraining conditions.…”
Section: Skeletal Muscle Changes During Resistance Trainingsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to the Co group, the Tr group exhibited a significant (P < 0.05) decrease in pure fiber IIA and IID CSA in the plantaris DR portion; there was also a tendency for pure fiber I and IIB CSA to decrease in this portion (P ¼ 0.08 and P ¼ 0.09, respectively). Our results are consistent with several studies which show a predominance of catabolic condition (Seene et al, 1999;Petibois et al, 2000;Seene et al, 2004) in situations with a persistent combination of excessive overload plus inadequate recovery (Jamurtas et al, 2000;Fatouros et al, 2006). Although the molecular events that underlie our findings remain unknown, these observations raise questions as to what signals and cellular conditions initiate muscle mass changes during overtraining conditions.…”
Section: Skeletal Muscle Changes During Resistance Trainingsupporting
confidence: 93%
“…Thus, progression from the benign adaptive microtrauma stage may exacerbate the initial injury (Stone et al, 1991) resulting in a subclinical injury in the overtrained athlete. Muscle injury induces a reduction in strength (Fatouros et al, 2006) due to extensive muscle damage (Seene et al, 1999), swelling in the injured area, soreness, edema (Jamurtas et al, 2000;Fatouros et al, 2006), and local inflammatory response (Smith, 2004). Also, Petibois et al (2003) demonstrated that overtrained individuals have higher amino acid and lower protein blood accumulation in response to exercise than welltrained individuals.…”
mentioning
confidence: 99%
“…However, few investigations of cf-DNA, as it relates to exercise and/or training, have been conducted. Recent studies of cf-DNA have explored the acute response of cf-DNA after a single bout of exercise [12][13][14][15][16][17] , as well as chronic changes in cf-DNA concentrations with resistance training 18 . These initial inquiries of post-exercise cf-DNA concentrations and training have suggested that cf-DNA may provide benefits over other markers of tissue damage and inflammation such as creatine kinase (CK) and C-reactive protein (CRP), for inclusion in a LTAMP.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological role of sFasL is controversial since it has been reported to induce non-apoptotic signals, possibly including NF-kβ-mediated stimulation of cell proliferation, survival or inflammation within an elevated cytokine milieu (Suda, et al 1997, Mogi, et al 2001, Serrao, et al 2001). In addition to FasL, circulating cell free DNA (cfDNA) has quite recently been discovered as a potential marker of inflammation, apoptosis, senescence and malignant conditions (Stroun, et al 1987, Fatouros, et al 2006, Jylhava, et al 2012). …”
Section: Introductionmentioning
confidence: 99%